Theorising the Islamic State: A Decolonial Perspective. (1st April 2018) - ,
Abstract : In this article, I engage with the current security debate on the conceptual understanding of the Islamic State (IS). I critically evaluate the dominant Western view within the debate that conceptualises IS as an "Islamic" terrorist organisation and a product of the "backwardness" of Islam and argue that such a conceptualisation of IS is rooted in a racist and Islamophobic Western epistemological narrative which seeks to create a "natural" link between terrorism and Islam. Through a conceptual discussion on terrorism and a critical assessment of the Eurocentric nature of security studies theories, both traditional and critical, I show how hegemonic Western epistemologies are able to conveniently ignore the European roots of terrorism in the foundation of Western modernity. One result is that hegemonic Western epistemologies are thus able to appropriate the concept of security as an exclusive domain of Western states and their societies, all the while carving out the non-European world, particularly Islamic societies, as the exclusive sources of potential terrorist threats. I, therefore, advance the decolonial theoretical concept of global coloniality as a means of reframing the debate and shifting the point of enunciation from dominant Western views of IS to a more critical Global South decolonial perspective. As such, I emphasise the European origins of terrorism as a constitutive element of the foundation of Western modernity, while addressing the cognitive confinement of security studies theories. In this light, the study concludes by asserting that IS is a creation of the constitutive violent logic of Western modernity/coloniality, which has terrorism as its foundational core.